2002
DOI: 10.1152/ajpendo.00058.2002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic basis of HIV-lipodystrophy syndrome

Abstract: Human immunodeficiency virus (HIV)-lipodystrophy syndrome (HLS) is characterized by hypertriglyceridemia, low high-density lipoprotein-cholesterol, lipoatrophy, and central adiposity. We investigated fasting lipid metabolism in six men with HLS and six non-HIV-infected controls. Compared with controls, HLS patients had lower fat mass (15.9 +/- 1.3 vs. 22.3 +/- 1.7 kg, P < 0.05) but higher plasma glycerol rate of appearance (R(a)), an index of total lipolysis (964.71 +/- 103.33 vs. 611.08 +/- 63.38 micromol x k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 36 publications
4
97
2
1
Order By: Relevance
“…However, we did find an increase in FFA turnover and clearance after treatment. Recently, Sekhar et al (42) provided strong evidence that the HLS is associated with increased FFA turnover and suggested that this reflected ongoing fat redistribution. Thus, the increased FFA turnover that we found in the absence of obvious lipodystrophy may be an early indicator for changes in lipid metabolism, which might eventually lead to the development of lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did find an increase in FFA turnover and clearance after treatment. Recently, Sekhar et al (42) provided strong evidence that the HLS is associated with increased FFA turnover and suggested that this reflected ongoing fat redistribution. Thus, the increased FFA turnover that we found in the absence of obvious lipodystrophy may be an early indicator for changes in lipid metabolism, which might eventually lead to the development of lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma FFA concentration is due to increased lipolysis (5,6), with increased net release of FFAs from adipose tissue (5,7). In other insulin-resistant states (e.g., obesity and type 2 diabetes), increased rates of lipolysis and plasma FFA concentration are related to the degree of insulin resistance (8 -10).…”
mentioning
confidence: 99%
“…Recent evidence (12,36,44) indicates that basal whole body lipolytic rate, intramyocellular lipid (IMCL), and hepatic lipid content are elevated in people with HIV-lipodystrophy who take protease inhibitor (PI)-including HAART. Although controversial (36), resting whole body fatty acid (FA) oxidation appears to be decreased in HIV-infected individuals with metabolic complications (22) and may be the result of HIVand/or nucleoside analog reverse transcriptase inhibitor-associated mitochondrial toxicity (21).…”
mentioning
confidence: 99%